Incidence and characteristics of surgical fistula patients at LAMB hospital from 2011 to 2017 - Ambauen-Berger, Beatrice; Saha, Stacy; Seadon, Alison (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To document the increasing trend of surgical fistulas seen at LAMB hospital and analyze the characteristics of these patients. Methods: Retrospective analysis of data entered into our database of 766 fistula patients seen at LAMB hospital from 2011-2017. The number and variables of surgical fistulas were focused upon. Fistulas occurring after LSCS only were considered surgical, if the Cesarean Section was elective or performed in early labour and the fistula did not have the characteristics of an obstetric fistula. Results: The total number of new fistula patients seen per year has remained stable at around 80. The proportion of surgical fistula has increased from 7% in 2011 to 45% in 2017. The percentage of patients who came with a fresh fistula (presenting within < 1 year) increased from 15% in 2011 to 47% in 2017 of which 33% and 80% respectively were surgical fistulas. 80% of surgical fistula occurred after abdominal hysterectomy, of which 78% are vault and 22% ureteric fistula. At least 50% of fistula occurred after an operation done without medical indication. 91% were performed in a private clinic. The majorities of patients with surgical fistula were of low socioeconomic status and had never attended school. Conclusions: While the number of obstetric fistulas is decreasing in Bangladesh, LAMB has seen an increase of surgical fistulas over the last 6 years, mainly caused by TAH. The majority of these operations are done in private clinics and there seems to be a lack of proper indication and surgical skills.